SURVIVAL ANALYSIS OF CUSTOMER IN POSTPAID TELECOMMUNICATION INDUSTRY - Doni Suhartono; Asep Saefuddin; I Made Sumertajaya (FORUM STATISTIKA DAN KOMPUTASI, 2013)
Currently, the business competition in mobile telecommunication industry among providers in Indonesia is tighter and it has given rise to a phenomenon of customer defection which has serious consequences for the business performance. In the current circumstances, customers are faced numerous options to be selected that probably cause them at risk to get churn. Therefore, it becomes one of the challenges encountered by Division of Loyalty and Retention to makes the efforts of decreasing customer defection. So that it is important conducting a model of churn practically applied to predict tendency of customer churn and also recognizing the prognostic factors influence customer churn. Survival analysis modelling, such as Cox’s proportional hazard model, was very successful in previous research, which investigatedthe relationship between survival time and possible prognostic factors. Based on the research, Cox’s proportional hazard model of customer lifetime is effective to distinguish relative risk between churn customers and others, and also between which loyal customers and with other short time customers with their significant prognostic factors. Afterwards the simulation of the survival probability estimated over time with particular possible combination of the most significant characteristics affecting tendency of churn, are able to predict such information of lifetime to churn event and compare the survival performance of one another. Finally, the results of this research is able to yield simple, helpful and applicable results as the principle of taking decission for optimizing their customer retention and/or treatment resources in their customer retention efforts for the company.Key words : Churn, Cox’s proportional hazard model, customer retention, survival analysis and telecommunication industry.